Lightweight Design and Finite Element Analysis of Brake Lever for Motorcycle Application - Agus Puji Prasetyono; Aan Yudianto; I Wayan Adiyasa (ComTech: Computer, Mathematics and Engineering Applications, 2023)
A lightweight component design contributes to the overall optimization of a system to be more effective and efficient. Then, it can lead to the contribution of a carbon footprint reduction. The research aimed to propose a novel lightweight brake lever design for motorcycle applications and numerically investigate its performance by comparing the proposed design with different utilized materials. The subject of the research was an optimized brake lever for motorcycle application. The materials used were aluminum alloy, structural steel, and titanium alloy. A Finite Element Method (FEM) analysis was employed to investigate the proposed brake lever design. Three proposed designs were introduced with the mass reduction in each optimization up to 50,9% of reduced mass. Maximum stress was observed on the most optimized design with a value of 297 MPa. The strain and total deformation were also investigated among the components. In the result, the stress-strain graph shows that the most optimized brake lever experiences the highest stress with the highest strain value. Furthermore, the highest safety factor is achieved with the utilization of titanium alloy, reaching the value of 6,28 for preliminary design and 3,1 for the most optimized component. However, the lightest component can be obtained using aluminum alloy.